Comparative evaluation of cleaning ability of reciproc and waveonegold reciprocating file systems - A scanning electron microscopic study - Jayaprada Reddy Surakanti; Rajani Punna; Amulya Vanapatla; Harikumar Vemisetty; Navya Poojitha Sajja; Tulasi Priya Nidumukkala (Wolters Kluwer Medknow Publications, 2018)
Objective: The aim of this study was to evaluate the canal cleaning ability of two reciprocating single file systems: Reciproc (VDW, Munich, Germany) and WaveOne gold (Dentsply Maillefer, Ballaigues, Switzerland) using scanning electron microscopy (SEM). Materials and Methods: Forty freshly extracted human mandibular premolar teeth with single root and canal were selected. The samples were randomly divided into two experimental groups (n = 15 each). Control group (n = 10) has non-instrumented teeth. Working length was determined using #10/15 K files. All the teeth were prepared to a # 25 final apical size following the manufacturer's instructions using crown-down technique. Teeth were sectioned buccolingually and examined under SEM at 20.0 kV and ×700 magnification. SEM images of the coronal, middle and apical third of the canal were taken and then analyzed using a five-score index. Results: The WaveOne Gold group presented a larger amount of debris than the Reciproc Group, however, without a statistically significant difference (P > 0.05). A larger amount of debris in the control group was observed, with the statistically significant difference between Reciproc and WaveOne Gold groups (P < 0.05). Conclusion: The two reciprocating single-file instrumentation systems presented similar effectiveness for root canal cleaning.